2015
DOI: 10.18088/ejbmr.1.1.2015.pp3-7
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Components of Wound Current at Mouse Skin Incisional Wounds

Abstract: It has been assumed that skin wound currents are produced by passive ion leakage from wounded skin. However, what ions contribute to the skin wound current? Thirty male C57BL/6 mice were used in this study. A lancet wound (about 5mm in length) was made by cutting into the full thickness skin. We measured the dynamic time courses of individual ion flux with ion-selective probes at skin wound. The probe is aligned perpendicular to the surface of skin wound. All ions , Ca 2+ and H + contribute to the wound curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
(37 reference statements)
3
8
0
Order By: Relevance
“…Our previous study confirmed that ions flux (Na + , Cl -, K + , Ca 2+ , H + ) contributes to mouse skin wound currents (1). In addition, we found that major ions flux of the wound current involved Na + and Cl -.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our previous study confirmed that ions flux (Na + , Cl -, K + , Ca 2+ , H + ) contributes to mouse skin wound currents (1). In addition, we found that major ions flux of the wound current involved Na + and Cl -.…”
Section: Introductionsupporting
confidence: 86%
“…Several previous studies have detec- ted wound current in various tissues in a variety of animals, including human skin (11)(12) and rodent cornea and skin (13)(14)(15)(16). In our previous study, we found that Clflux was the main ionic flux and major contributor to the skin wound current (1). The results of our study demonstrated that Clflux increased significantly after mouse skin was incised compared to that in normal skin.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Ideally, any biological system of interest should be studied with the minimum interference and under the most physiological condition possible. Such criteria are attained by the non-invasive ion-selective vibrating probe, which has been used for measuring multiple transmembrane ion fluxes in a wide variety of experimental systems, including Drosophila (Browne and O'Donnell, 2016), zebrafish (Guh et al, 2016), mouse skin (Sun et al, 2015), roots (He et al, 2015), Daphnia (Stensberg et al, 2014), C. elegans (Adlimoghaddam et al, 2014), etc. In pollen tubes, quantitative measurements of extracellular ion fluxes using the ion-selective vibrating probe have been fundamental in establishing the role of major ions (especially Ca 2+ , H + , K + , and anions) in apical growth.…”
mentioning
confidence: 99%